Repeatability and heritability of objective and subjective fleece traits and body weight in South African Angora goats - Snyman, M.A.; Olivier, J.J. (Elsevier, 1999)
The repeatability and heritability of body weight, greasy fleece weight and mean fibre diameter, as well as various subjective fleece traits of South African Angora goats were estimated. The first of two data sets analysed, was collected through the Angora goat performance-testing scheme (AGPTS), while the second comprised data collected on the experimental flocks kept at the Jansenville Experimental Station (JEF). The following traits were assessed subjectively on a linear scale ranging from 1 to 50 at the second, third and fourth shearings, namely fullness of face covering, fullness of the neck, fullness of belly and points, style, character, evenness of fleece, softness of face and ears, pigmentation in the face and on the ears, and kemp and medullated fibres. Heritability and repeatability estimates were obtained by fitting repeatability animal models under a DFREML programme. Heritability for body weight was higher in the JEF (0.47±0.01) than in the Angora studs (0.35±0.05), while the same heritabilities were estimated for fleece weight (0.22±0.04) and fibre diameter (0.30±0.05) in both data sets. The repeatability of body weight was higher in the JEF (0.63) than in the studs (0.53), but it was lower for weight (0.27 vs. 0.41) and fibre dianleter (0.35 vs. 0.68) in the JEF. Heritability and repeatability estimates for all subjectively assessed traits, with the exception of face cover in the JEF and pigmentation in both data sets, were moderate, too. Due to the fact that young bucks in South Africa are sold at 14-16 months of age with their full third fleece, perfornance has to be done at 8-9 months of age at the second shearing. As fleece weight had the lowest repeatability of the three production traits, it was recommended that the fleece weight be left out of the selection index. The possible inclusion of style in the selection index needs to be investigated further. As far as the other subjectively assessed traits are concerned, it is recommended that any selection for the further improvement of these traits should be based on independent culling levels and they could not be included in the selection index.